AN IDEOLOGICAL COMMUNICATION BETWEEN L’ETRANGER” BY ALBERT CAMUS AND IWAN SIMATUPANG’S “ZIARAH” - Sunahrowi Sunahrowi (Universitas Negeri Makassar, 2020)
This research aims to describe literary communication betwen Indonesian and French literary works. The literary communications of the romances by Indonesian and French authors, particularly in this study between the romances by Albert Camus and Iwan Simatupang provided all possible significant effects that emerged from earlier work to the next work. The research method applied to analyze data is the semiotic method. This research resulted in a finding that was related between two literary work of different countries, Indonesia and France, mainly related to the structure of the story, characterizations, settings of time and place. The two works were also produced by two authors who have the same world views and ideology, namely existentialism. The literary communication that flies between the two literary works is based on the structure of work and at the same time the ideology underlying it.